Visual symbolism and the art design nexus in madness: A critical discourse analysis of Penahitam’s subcultural artzine in Indonesia - Wibawa, Mahendra; Sunarto, Bambang; Murtono, Taufik (International Journal of Visual and Performing Arts, 2025)
This study examines how hybrid visual practices in subcultural contexts challenge the binary between art and design. It addresses the theoretical division proposed by Tsion Avital, who posits a strict dichotomy between symbolic art and functional design. Using this framework, the visual discourse of the Indonesian collective Penahitam is critically analyzed. The 9th edition of Penahitam's artzine, Madness, is selected as a case study due to its thematic depth and ideological complexity. The research applies Norman Fairclough’s Critical Discourse Analysis (CDA) to integrate textual, visual, and contextual elements, exploring how meaning is constructed through the interplay of image, text, layout, and cultural production. Avital’s symbolic-functional theory serves as a lens to assess how Penahitam negotiates between expressive freedom and visual functionality. Findings indicate that Madness reconfigures the relationship between artistic and design elements into a hybrid visual discourse. The artzine's layout, poetic writing, dark-art illustrations, and socio-political content work cohesively to communicate ideological resistance while remaining accessible. This integration disrupts Avital’s dichotomy, showing how hybridity becomes a strategic tool for expression and subcultural authorship. Furthermore, the production and dissemination of the artzine across 29 Indonesian cities underscore Penahitam’s commitment to collective authorship, independence, and decentralized cultural activism. This study contributes to the discourse on art-design hybridity by offering a concrete analytical model for understanding how independent collectives use visual media to challenge dominant narratives and assert creative autonomy.